The Role of Socialization, Effortful Control, and Ego Resiliency in French Adolescents’ Social Functioning - Hofer, Claire (2010)
The relations among effortful control, ego resiliency, socialization, and social functioning were examined with a sample of 182 French adolescents (14–20 years old). Adolescents, their parents, and/or teachers completed questionnaires on these constructs. Effortful control and ego resiliency were correlated with adolescents’ social functioning, especially with low externalizing and internalizing behaviors and sometimes with high peer competence. Furthermore, aspects of socialization (parenting practices more than family expressiveness) were associated with adolescents’ effortful control, ego resiliency, and social functioning. Effortful control and ego resiliency mediated the relations between parental socialization and adolescents’ peer competence and internalizing problems. Furthermore, effortful control mediated the relations between socialization and adolescents’ externalizing behavior. Findings are discussed in terms of cultural and developmental variation.